2018
DOI: 10.1038/s41598-018-22285-x
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study on efficacy of rupatadine for the treatment of acute dengue infection

Abstract: Currently there are no specific treatments available for acute dengue infection. We considered that rupatadine, a platelet-activating factor receptor inhibitor, might modulate dengue-associated vascular leak. The effects of rupatadine were assessed in vitro, and in a dengue model, which showed that rupatadine significantly reduced endothelial permeability by dengue sera in vitro, and significantly inhibited the increased haematocrit in dengue-infected mice with dose-dependency. We conducted a randomised, place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 44 publications
(53 reference statements)
2
30
0
4
Order By: Relevance
“…20 PAF was previously found to be an important contributor to vascular leak and PAF receptor blockade was found to inhibit the effects of acute dengue sera on the expression of the tight junction protein ZO-1, and in the reduction of trans-endothelial resistance. 15 Endocytosed DENV like particles has been proven by ultrastructural analysis of platelets from patients with dengue. In vitro studies identified the mechanisms of DENV binding and internalization by platelets requiring DC-SIGN and heparan sulfate proteoglycans for viral attachment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…20 PAF was previously found to be an important contributor to vascular leak and PAF receptor blockade was found to inhibit the effects of acute dengue sera on the expression of the tight junction protein ZO-1, and in the reduction of trans-endothelial resistance. 15 Endocytosed DENV like particles has been proven by ultrastructural analysis of platelets from patients with dengue. In vitro studies identified the mechanisms of DENV binding and internalization by platelets requiring DC-SIGN and heparan sulfate proteoglycans for viral attachment.…”
Section: Discussionmentioning
confidence: 99%
“…Other mediators that are known to cause vascular leak include bradykinins, complement proteins C3a and C5a, IL-33, fibrin products, prostaglandins E2, F2a, and D2. 15 Hemorrhagic manifestation in Dengue virus Infection patients are not common and within mild to severe. Skin hemorrhage, including petechiae and purpura, are the most common, along with gum bleeding, epistaxis, menorrhagia, and gastrointestinal bleeding.…”
Section: Mcp-1/ccl2mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore rupatadine might modulate dengue-associated vascular leak acting through PAF receptors. A randomised, placebocontrolled trial in 183 adult patients in Sri Lanka with acute dengue, showed that rupatadine up to 40 mg daily appeared to be safe and well-tolerated with minimum adverse events [42]. Higher platelet counts and lower transaminase levels on day 7 were seen in the rupatadine group compared to the placebo.…”
Section: Newer Therapeutic Modalities In Secondary Preventionmentioning
confidence: 99%
“…Higher platelet counts and lower transaminase levels on day 7 were seen in the rupatadine group compared to the placebo. Authors concluded that the potential beneficial effect of rupatadine requires further evaluation in large studies focused on recruitment during the early febrile phase [42].…”
Section: Newer Therapeutic Modalities In Secondary Preventionmentioning
confidence: 99%